2020
DOI: 10.1093/jnci/djaa002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neoadjuvant Chemotherapy in Patients With Resectable Malignant Pleural Mesothelioma—An Institutional and National Analysis

Abstract: Background There is no standard of care with respect to the use of neoadjuvant chemotherapy (NAC) in resectable malignant pleural mesothelioma (MPM). We performed an intention-to-treat analysis with data from a single institution and the National Cancer Database (NCDB) to identify whether the use of NAC impacts survival in resectable MPM. Methods Patients with MPM who had surgery with curative intent at Duke University from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In this propensity score matched retrospective analysis, 22 patients with malignant pleural mesothelioma were treated with induction chemotherapy consisting of platinum-based/ pem with bevacizumab prior to surgery compared to 66 patients receiving standard induction chemotherapy with platinum-based/pemetrexed alone. Whereas the concept of a multimodality treatment is widely accepted and recommended for this disease, the timing of chemotherapy before or after surgery is discussed controversially (1,10,11) and currently investigated in a multicenter randomized phase II trial by the In the present analysis, adding bevacizumab to standard induction chemotherapy did not significantly increase perioperative, in particular not bleeding, complications, although the proportional number of postoperative blood products and PE were higher compared to the control group. The small sample size and the lack of randomization do not allow to draw any conclusion to fully answer this question as well as the fact that PE is in general a known side effect of also the other chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In this propensity score matched retrospective analysis, 22 patients with malignant pleural mesothelioma were treated with induction chemotherapy consisting of platinum-based/ pem with bevacizumab prior to surgery compared to 66 patients receiving standard induction chemotherapy with platinum-based/pemetrexed alone. Whereas the concept of a multimodality treatment is widely accepted and recommended for this disease, the timing of chemotherapy before or after surgery is discussed controversially (1,10,11) and currently investigated in a multicenter randomized phase II trial by the In the present analysis, adding bevacizumab to standard induction chemotherapy did not significantly increase perioperative, in particular not bleeding, complications, although the proportional number of postoperative blood products and PE were higher compared to the control group. The small sample size and the lack of randomization do not allow to draw any conclusion to fully answer this question as well as the fact that PE is in general a known side effect of also the other chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 56%
“…In this propensity score matched retrospective analysis, 22 patients with malignant pleural mesothelioma were treated with induction chemotherapy consisting of platinum-based/pem with bevacizumab prior to surgery compared to 66 patients receiving standard induction chemotherapy with platinum-based/pemetrexed alone. Whereas the concept of a multimodality treatment is widely accepted and recommended for this disease, the timing of chemotherapy before or after surgery is discussed controversially ( 1 , 10 , 11 ) and currently investigated in a multicenter randomized phase II trial by the EORTC [The European Organization for Research and Treatment of Cancer (NCT 02436733)].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, at this time, post-operative radiotherapy is usually neither feasible nor effective in the post-operative setting. An analysis of the National Cancer Data Base (n=1,949) as well as the Duke University database (n=257) in 2020 failed to demonstrate any benefit from induction therapy (20). In fact, it reached the opposite conclusion, demonstrating that induction therapy actually increased post-resection mortality (HR =1.29 for the NCDB data, HR =1.62, for propensity matched data).…”
Section: Induction Therapymentioning
confidence: 99%
“…Neoadjuvant treatments have been the object of active investigation, yielding mixed results. As a whole, neoadjuvant chemotherapy granted no survival advantage ( Voigt et al, 2020 ). Neoadjuvant radiotherapy was recently evaluated in a phase II trial (SMART), that showed only the feasibility of this technique ( Cho et al, 2021 ).…”
Section: Current and Upcoming Standard Of Carementioning
confidence: 99%